Social Media and Website Use by Muslim Organisations and Actors Across Diverse European Contexts: Preliminary Results from the Digital Islam Across Europe Research Project - Grasso, Anna (Digital Muslim Review, 2025)
This article presents preliminary findings from the Digital Islam Across Europe (DigitIs- lam) project, examining how Muslim organisations and actors utilise websites and social media across five European countries. Combining macro-level web archival analysis of approximately 1,000 websites with micro-level qualitative interviews and a quantitative survey of UK Muslim producers and users, the research investigates the distinct functions of digital platforms. At the European level, findings reveal that websites primarily serve formal, archival communication, while social media functions as the dominant tool for engagement and mobilisation, with notable national variations. In the UK, qualitative interviews demonstrate producers’ strategic adaptation to platform-specific affordances, balancing curated websites with rapid social media interactions. Survey data indicates high daily social media consumption alongside continued trust in traditional offline authorities and structured online resources for authoritative religious knowledge. The study identi- fies a disconnect between institutional strategies and everyday user practices, contributing nuanced understanding of shifting religious authority in Online Islamic Environments.